Reproductive ability of triploid ornamental (koi) carp (Cyprinus carpio L.) × goldfish (Carassius auratus L.) hybrids and characteristics of their offspring. (6th April 2020) - Kramer, Alexander G.; Gomelsky, Boris; Warner, Jeffrey L.; Novelo, Noel D.; Thomas, Brandylyn L.
Abstract: The purpose of this study was to investigate reproductive ability of backcross triploid koi ( Cyprinus carpio L.) × goldfish ( Carassius auratus L.) hybrids. These triploids have been obtained by crossing of F1 hybrid females producing diploid eggs with males of parental species. Triploid hybrid females, when crossed with goldfish or koi males, produced mostly aneuploid fish with ploidy range from approximately 2.2n–3.2n with a mean value 2.5n; some fish in crosses of triploid females with koi males were tetraploid (4.0n). Since analysed fish had in their genomes one haploid set from parental males, the data indicate that triploid hybrid females mostly produced aneuploid eggs with ploidy range from approximately 1.2n–2.2n and a mean ploidy around 1.5n while some eggs were triploid. Triploid hybrid males were completely sterile and have not released any sperm after hormonal injection. Despite their low viability, some aneuploid fish obtained from triploid hybrid females were raised in indoor recirculating systems until the age of 2 years and their reproductive ability has been evaluated. One aneuploid female with ploidy 2.1n produced larvae with ploidy range from 2.9n to 3.4n with a mean ploidy of 3.1n when crossed with a koi male; about 60% of obtained larvae had ploidy from 3.0n to 3.2n. These data indicate that this female produced mostly eggs with unreduced ploidy level.